Occult Intraamniotic Infection at the Time of Midtrimester Genetic Amniocentesis: A Reassessment - Peter H. Cherouny; Glenn A. Pankuch; John J. Botti (Hindawi Limited, 1994)
Objective: The objective of this study was to reevaluate the incidence of occult early midtrimester intraamniotic infection in asymptomatic patients at the time of genetic amniocentesis.